LEGAL AND FINANCIAL WORK ASPECTS OF ACADEMIC STAFF IN LITHUANIA, SLOVAKIA AND LATVIA - Mietule, Iveta; Skėruvienė, Vitalija; Ubrežiova, Iveta; Znotiņa, Daina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The legal and financial work aspects of academic staff have been insufficiently studied. Basically, it is the existing autonomy of each university personnel policy. The variety of diverse approaches exists not only in different countries, but also within the borders of one particular country. The research aims to provide an evaluation of the legal and financial work aspects of the academic staff in Lithuania, Slovakia and Latvia. In the framework of this research a comparative analysis of all three countries’ legislation has been performed, reflecting common and distinctive features of the academic staff requirements, as well as general principles of salary formation have been evaluated.